The Association Between Conditional Cash Transfer and Fertility Intention in Indonesia - Rafly Parenta Bano; Omas Bulan Samosir; Triasih Djutaharta (Jurnal Ilmu Sosial dan Ilmu Politik, 2021)
This study aims to analyze the relationship between conditional cash transfer (PKH in Indonesia)acceptance status and fertility intentions of married women ages 15-49 years who do not use contraception in Indonesia. The data used in this research comes from the results of SUSENAS 2017. The sample was limited to married women aged 15-49 years not currently using a contraceptive method. Ordinal logistic regression was employed to analyze the relationship between PKH acceptance status and fertility intention after controlling for the effects of individual control factors, while a multilevel ordinal logistic model was used to investigate the effects of contextual factors. The study results showed that after controlling for the effects of individual and contextual variables, a high fertility intention was associated with receiving PKH. Women from PKH beneficiary households tended to maximize the assistance received by increasing the number of children (moral hazard behavior ). Moral hazard behavior was more pronounced in women from households that had received PKH or received PKH but could not show their cards.